Genetic Variability of Rice Pericarp Color Parameters and Total Anthocyanine Content of Eleven Local Black Rice and Their Correlation - Kristamtini, Taryono, Panjisakti Basunanda, dan Rudi Hari Murti (Jurnal Ilmu Pertanian, 2014)
ABSTRACTBlack rice starts to be consumed as functional food due to high anthocyanine content which functioned as an antioxidant. The different in an existing name is predicted due to the pericarp color differences which are from light to heavy black.  It is therefore that morphological characteristics observation of pericarp color is required. This study aimed to identify genetic variability of 11 Indonesian local cultivar of black rice based on pericarp color parameters and total anthocyanine content, even their correlations. L*,  a*, b* color parameters were observed using Chroma Meter -  Konica Minolta – Minolta CM-2006, and white standard color was used for calibration, whereas total anthocyanine content was measured based on absorbent value of grinded rice grains using 535 nm wavelength of spectrophotometer. Color parameters and total anthocyanine content data were analyzed using analysis variance to estimate Genetics Variability Coefficient and cluster analysis to know the similarity among these local cultivars of black rice. The result showed that b* color variable and total anthocyanine content indicate broad genetic variability, whereas L* and a* color variables depict narrow genetic variability. There were 3 different groups of black rice based on   L*, a* and b* color parameters and total anthocyanine content. These were Cempo ireng; Banjarnegara, Banjarnegara-Wonosobo, Magelang berbulu, Magelang tak berbulu, Nusa Tenggara Timur and Pari Ireng; and Sragen, Jlitheng, Bantul and Melik groups. Positive significant correlation was observed between L*, a*, b* color parameters, and there was negative significant correlation between total anthocyanine content and L*, a*, dan b* color parameters. Key words: genetic variability, pericap colour parameters, total anthocianin content, local black rice